Assessment of malnutrition among the internally - displaced old age people in the Tikrit City, Iraq - Ibrahim, Nisreen M; Khalil, Nawar Sahib; Tawfeeq, Ruqaya Subhi (Journal of Ideas in Health, 2019)
Background: With the steady increase in the number of old age people, the prevalence of chronic diseases, and the health expenditures, the importance of preventing malnutrition is becoming more critical than ever. This study aimed to assess malnutrition among the internally- displaced old age people in Iraq. Methods: A descriptive cross-sectional study conducted between November 2016 and March 2017 at the Dream city camp for the internally - displaced persons in Tikrit city, Iraq. Data was collected using the valid (Arabic) version of the mini - nutritional assessment (MNA) questionnaire. The internally displaced persons (IDPs) interviewed, and the nutritional status assessed via the MNA, body mass index (BMI), mid-arm circumferences (MAC) and calf circumferences (CC) measures. Results: A total of 142 eligible old age persons, of which 40.2% were malnourished, and 35.2% were at risk of malnutrition. Among those with malnutrition, 40% were males, and 60% were females. Concerning comorbidity, 80% with positive malnutrition, had chronic diseases. DM reported a higher prevalence (46.5%) compared to other chronic diseases. Conclusion: The prevalence of malnutrition was high among the old age people resident at the displacement camp in Iraq. Both the deteriorating security situation and the lack of proper services have combined to exacerbate the nutritional status of older persons in displacement camps.